Breaking Barriers: Women's Political Mobilization in Rural Village Head Elections - Pravidjayanto, Mochammad Rafi (Nursyam Centre, 2024)
This article describes the victory of female village head candidates in village head elections as a rare occurrence, mainly due to the lack of access for women to leadership positions due to a solid patriarchal culture. However, after being elected, women proved to have the competence to lead, showing that women can become leaders at the village level. Cultural shifts, especially in Javanese culture, have allowed women to be involved in the public sphere, including in organizations such as the the Pemberdayaan dan Kesejahteraan Keluarga (PKK), Dasawisma, and others. This paper uses a qualitative approach and case studies to examine the phenomenon. Data were obtained through observation, dialogue, and in-depth interviews. The results show that women can gather and mobilize political power from multiple sources to influence voters and dominate the dynamics of village democracy. Habitus of leadership, symbolic dominance, hegemony of social institutions, and kinship became the main instruments utilized by female village head candidates. They draw on leadership experience in social solid and kinship institutions to win village head elections.